Behavioural Insights into Dairy Farmers’ Adoption of Feeding Innovations - Reproto, Ronel O.; Barrio, Arnel N. Del; Sevilla, Cesar C.; Calalo, Filma C.; Angeles, Amado A. (Journal of Buffalo Science, 2024)
The Philippine Carabao Center (PCC) has promoted various feeding innovations to enhance buffalo-based dairy enterprise and increase milk production, yet adoption rates have been suboptimal. This study explores the decision-making processes of dairy farmers regarding the adoption of these innovations, focusing on how attitudes and subjective norms influence their intentions to implement PCC-endorsed feed technologies, such as improved forage, concentrate feeding, legume supplementation, and forage ensiling. Data were collected through structured interviews with 60 dairy farmers. The analysis was conducted using the Statistical Package for Social Sciences (SPSS). Results showed that socioeconomic factors and farm characteristics minimally impact the intention to adopt innovations, with land ownership and herd size positively influencing concentrate feeding. Perceived usefulness and difficulty significantly shape farmers’ intentions, indicating that constraints like land availability and high production costs hinder the adoption of legume supplementation and forage ensiling. While attitudes toward feeding innovations are generally positive, practical challenges limit their uptake. Social norms, shaped by extension staff and peer farmers, play a significant role in influencing farmers’ intentions to adopt these innovations. This study emphasized the need to address practical barriers to enhance the uptake of feeding innovations and improve dairy buffalo production.